2019
DOI: 10.1051/0004-6361/201834100
|View full text |Cite
|
Sign up to set email alerts
|

ALMA reveals the magnetic field evolution in the high-mass star forming complex G9.62+0.19

Abstract: Context. The role of magnetic fields during the formation of high-mass stars is not yet fully understood, and the processes related to the early fragmentation and collapse are as yet largely unexplored. The high-mass star forming region G9.62+0.19 is a well known source, presenting several cores at different evolutionary stages. Aims. We seek to investigate the magnetic field properties at the initial stages of massive star formation. We aim to determine the magnetic field morphology and strength in the high-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 93 publications
(115 reference statements)
2
12
0
Order By: Relevance
“…A milliGauss magnetic field amplitude is consistent with estimates in other massive star forming regions (e.g. Girart et al 2013;Dall'Olio et al 2019;Beltrán et al 2019). Last but not least, Girart et al (2009) and Qiu et al (2014) concluded that their observations are consistent with magnetic braking; that is, a magnetically regulated collapse.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A milliGauss magnetic field amplitude is consistent with estimates in other massive star forming regions (e.g. Girart et al 2013;Dall'Olio et al 2019;Beltrán et al 2019). Last but not least, Girart et al (2009) and Qiu et al (2014) concluded that their observations are consistent with magnetic braking; that is, a magnetically regulated collapse.…”
Section: Introductionsupporting
confidence: 82%
“…There is no clear consensus on which physical process regulates the fragmentation level. There is, however, a trend in which massive dense cores are not as fragmented as expected (Wang et al 2014;Csengeri et al 2017;Nony et al 2018) and magnetic fields have an important role in fragmentation (Li et al 2015;Dall'Olio et al 2019). Using state-of-the-art multi-dimensional and multiphysics numerical models, it has also been demonstrated that magnetic fields, radiative transfer, and turbulence all play role in setting the fragmentation level of massive star forming regions (Hennebelle et al 2011;Commerçon et al 2011b;Myers et al 2013;Fontani et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A mG magnetic field amplitude is consistent with estimates in other massive star forming region (e.g. Girart et al 2013;Dall'Olio et al 2019;Beltrán et al 2019). Last but not least, Girart et al (2009) and Qiu et al (2014) conclude that their observations are consistent with magnetic braking, i.e.…”
Section: Introductionsupporting
confidence: 84%
“…There is no clear consensus on which physical processes is regu-lating the fragmentation level. There is however a trend in which massive dense cores are not as fragmented as expected (Wang et al 2014;Csengeri et al 2017;Nony et al 2018), and that magnetic fields has an important role in the fragmentation (Li et al 2015;Dall'Olio et al 2019). Using state-of-the-art multidimensional and multi-physics numerical models, it has also been demonstrated that magnetic fields, radiative transfer and turbulence all play role in setting the fragmentation level of massive star forming regions (Hennebelle et al 2011;Myers et al 2013;Fontani et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We then confirm the 60 cores as hot cores, and give their coordinates, rotation temperatures and column densities in Table 1. We have checked the literature and found that 15 of these hot cores have been reported before (I18089-1732, Beuther et al 2004;I18032-2032I18032- /G9.62+0.19, Liu et al 2015Dall'Olio et al 2019;I18507+0110/G34.43+0.24, Beltrán et al 2009;Fu & Li 2017;Calcutt et al 2014; I17441-2822/Sgr B2(M), Sánchez-Monge et al 2017;IRAS18056-1952/G10.47+0.03, Rolffs et al 2011; I18507+0121/G34.26+0. 15 , Sakai et al 2013;Mookerjea et al 2007;I16060-5146, I16065-5158, I12326-6245, I14498-5856, I15254-5621, Araya et al 2005;Dedes et al 2011;I16547-4247, I17233-3606, I18182-1433, Hernández-Hernández et al 2014I17175-3544/NGC6334I, Brogan et al 2016).…”
Section: Line and Hot Core Identificationsmentioning
confidence: 69%